2007
DOI: 10.1007/s11430-007-2051-z
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic evolution of the Western Kunlun orogenic belt in northern Qinghai-Tibet Plateau: Evidence from zircon SHRIMP and LA-ICP-MS U-Pb geochronology

Abstract: The Western Kunlun Range in northern Qinghai-Tibet Plateau is composed of the North Kunlun Terrane, the South Kunlun Terrane and the Karakorum-Tianshuihai Terrane. Here we report zircon SHRIMP and LA-ICP-MS U-Pb ages of some metamorphic and igneous rocks and field observations in order to provide a better understanding of their Precambrian and Palaeozoic-early Mesozoic tectonic evolution. Based on these data we draw the following conclusions: (1) The paragneisses in the North Kunlun Terrane are likely of late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 32 publications
3
57
0
Order By: Relevance
“…Therefore, the Paleoproterozoic rocks in either the North Kunlun or the Tianshuihai terranes, or both of them, are likely the detrital sources for the Tianshuihai metasedimentary rocks.Regarding the zircon age population of 2076-1644 Ma (small peaks: ca. 2051 and 1835 Ma), a few metamorphic ages of 1900 ± 12 Ma (gneissic granite) (Zhang et al, 2003c(Zhang et al, , 2007 and 2016 ± 39 Ma (meta-volcanic rocks) have been reported in the North Kunlun and Tianshuihai terranes. The 2000-1830 Ma metamorphic event have been widely recognized in the North Kunlun terrane (Wang, 2011).…”
Section: Provenance and Depositional Age And Of The Meta-siliciclastimentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the Paleoproterozoic rocks in either the North Kunlun or the Tianshuihai terranes, or both of them, are likely the detrital sources for the Tianshuihai metasedimentary rocks.Regarding the zircon age population of 2076-1644 Ma (small peaks: ca. 2051 and 1835 Ma), a few metamorphic ages of 1900 ± 12 Ma (gneissic granite) (Zhang et al, 2003c(Zhang et al, , 2007 and 2016 ± 39 Ma (meta-volcanic rocks) have been reported in the North Kunlun and Tianshuihai terranes. The 2000-1830 Ma metamorphic event have been widely recognized in the North Kunlun terrane (Wang, 2011).…”
Section: Provenance and Depositional Age And Of The Meta-siliciclastimentioning
confidence: 99%
“…The protoliths to the Precambrian metamorphic rocks had undergone amphibolite facies metamorphism in the Neoproterozoic (ca. 1.0-0.9 and 0.8 Ga) (Matte et al, 1996;Yuan et al, 2002Yuan et al, , 2003Xiao et al, 2003;Zhang et al, 2003aZhang et al, , 2007. The basement is overlain by a low-grade metamorphosed Upper Neoproterozoic (Sinian; ca.…”
Section: Regional Geologymentioning
confidence: 99%
See 3 more Smart Citations